A contribution to the Odonata fauna of Moala Island, Fiji. Part I: erection of three new species in genera Nesobasis Selys, 1891 and Nikoulabasis Ferguson et al., 2023 (Odonata: Coenagrionidae) - Marinov, Milen; Rashni, Bindiya (Zootaxa, 2025)
This study records the first members of Nesobasis Selys, 1891 and Nikoulabasis Ferguson et al., 2023 from Moala Island, Fiji. Three new species were erected for the following endemics: Nesobasis delai, sp. nov. (holotype male, headwater system, a tributary of Waitabu Lake), Nesobasis malokuensium, sp. nov. (holotype male, tributary of Wailevu Creek above Maloku village) and Nikoulabasis pauta, sp. nov. (holotype female, section of Wailevu creek about 500 m above Maloku village up to the Savukaratu waterfall). Three discussion points are outlined for future studies: phenology, female bias sexual ratio and biogeography.